Człowiek jako swojość i obcość – „słaby” projekt etyczny - Walczak, Anna (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2017)
In this article, I undertake the issues of a human as a liminal being in the sphere of experiencing one’s subjectivity and strangeness. At the same time, I acknowlege that constructing one’s identity in the process of narration a human being should be open to the experience of subjectivity and strangeness in the category of event. This experience leads a human being to recognising and understanding oneself as a liminal being who, „exposing oneself ” to one’s way of being - creating a project of being oneself, defined as an ethical project, „proves” one’s fragility, transience et cetera. I ask a question whether a person defined as a „weak subject” who creates oneself as a „weak” ethical project, in which terms there are presumptions of „weak thought” of Gianni Vattimo can become a challenge to „re-thinking” anthoropological contexts in pedagogy and education.
Keywords: ethical project; event; pedagogy; subjectivity; strangeness; weak thought